Lean and Six Sigma practices in the public sector: a review. Issue 3 (11th February 2019) - Rodgers, Bryan; Antony, Jiju
Abstract : Purpose: The purpose of this paper is to provide a critical analysis of publications relating to the use of continuous improvement (CI) methodologies, such as Lean, Six Sigma and Lean Six Sigma over a 17-year period, to identify the themes and gaps, while informing the development of a future research agenda. Design/methodology/approach: The systematic literature review identified 121 papers published between 2000 and 2017 from searches of over 1, 400 peer-reviewed academic journals and also identified the application of Lean, Six Sigma and Lean Six Sigma across the public sector. Findings: This research compares the scale and breadth of the public sector with the application of CI methodologies and finds that such application is unstructured and, in some areas, sporadic. The research identifies common themes and research gaps including areas such as lack of shared understanding of Lean, gaps in strategy development and leadership and an overfocus on tools alone. Research limitations/implications: The methodology is focussed on the journals rated in the ABS Journal Guide 2015, which allowed manual searches for accuracy and relevance to the area of investigation. It is recognised that this may exclude some articles which have been published in other journals but allowed for a structured and detailed investigation. The research identifies some very clear gaps which can inform future research agendas. Practical implications: The paper details the implications and challenges to the public sector, generally, and to executive leadership, specifically, and, in particular, covers the common issues and concerns, which in turn will assist public sector organisations in implementing, reviewing or refreshing their CI initiatives. Originality/value: No similar work has been conducted and while some individual areas such as health and education have been the subject of more focus, this research explores the public sector as a whole and considers the patterns of research in that context.